KETIDAKADILAN GENDER DALAM CERPEN QISSATU FATHIYAH AL MISRIYYAH DALAM ANTOLOGI CERPEN ADAB AM QILLATU ADAB NAWAL SA’DAWI - Mamdukh Budiman (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2012)
Literature is an activity or human behavior, both forms of verbal or physical, that seek to be understood by science. It is a fact of human activity that gave rise to a certain social activities, political activity, as well as the cultural creatives such as philosophy, art movement, art, sculpture, music, literature and other art. Teuw has argued that literature is placed fourth after religion, philosophy, science and discipline. Majazi literature, is the result of the power of reason and imagination that are high, so the form will be contained in the form of creative literature with the stage of creativity and initiative, if it deals with literature, essentially an exploration of creativity and thought to literary works that are created, resulting in the psychological elements will affect the creation of literary works, both from the impact of emotions, as well as the impact of the motif. According to Sangidu, things were with literary term for Indonesia community, which consists of concepts that are not causing the problem, though it is never stated in a clear and unequivocal statement. This can be seen in situations that do not give a rise to discuss about the use of scientific (Sangidu, 2004:31). To understand the essence of literary work that requires some steps that are not always easy to understand the goals, and the necessary steps should be taken before a thorough understanding to level, with an understanding of hermeneutics, and mastered various systems is a fairly complex code, either language or culture code, as well as literature with unique code. Key Words: Majazi literature, feminism, gender injustice.